The roles of social influences on student competence, relatedness, achievement, and retention in STEM. Issue 4 (20th May 2018) - Hilts, Alexis; Part, Rachel; Bernacki, Matthew L.
Abstract: Students' perceptions of competence and relatedness are known to influence learning processes and achievement, and may have particular import for underrepresented science, technology, engineering and mathematics (STEM) learners. Sources of social support that contribute to undergraduate life science learners' perceived competence and relatedness were examined, as were achievement and retention outcomes influenced by these sources of support and self‐determination theory components. Female, ethnically underrepresented, or first‐generation students reported similar levels of perceived competence and relatedness in STEM compared to their majority counterparts at a large, urban university. However, social supports, competence, and relatedness were differentially important for these subgroups as predictors of achievement and intention to leave a science major. For the full sample, competence perceptions predicted greater achievement and lessened intentions to leave a major. Competence perceptions were primarily derived from contact with classmates, especially for underrepresented groups. Feelings of relatedness were specifically important for the retention of women pursuing science degrees. Contacts with STEM peers and classmates were sources of relatedness for majority groups, but classmate contact was not significant for underrepresented groups. Findings highlight the value of promoting competence and relatedness and the differing sources that these subgroups draw on to build the perceived competence and relatedness that can predict achievement and retention.